Coordenação fina e escrita de crianças de 6 a 9 anos nascidas a termo e pré-termo: estudo descritivo - Coronado, Natália Barbosa (Universidade Federal de São Carlos, 2014)
Handwriting acquisition is an important factor for good school performance that due to motor components required for its execution may be compromised in schoolchildren born preterm. OBJECTIVES: To investigate the relationship between fine motor coordination and the quality of handwriting in school age children born preterm and full term. METHOD: This was a descriptive study wit group comparison, the study group was composed of students of both genders, preterm infants between born in 2004, 2005 and 2006 with gestational age between 32 and 36 weeks, birthweight ≤ 2500g, and the comparison group, with children born during the same period, with gestational age ≥ 37 weeks, birth weight ≥ 2500g, which were matched according to gender, age, socioeconomic status, and school level. The study was conducted in a small town in the interior of São Paulo state and the study was approved by the ethics committee and the town´s Departments of Health and Education. Parents or guardians from both groups were interviewed to collect personal data and information on family dynamics and socioeconomic status and they responded to the questionnaires Developmental Coordination Disorder Questionnaire (DCDQ Brazil), the Brazil Criteria for Economic Classification (CCEB), and the Parents Questionnaire of the Avaliação da Coordenação e Destreza Motora (ACOORDEM). The children fine motor skills were assessed with the ACOORDEM and the classroom teachers responded the ACOORDEM´s Teacher´s Questionnaire as well as the Escala de Transtorno de Déficit de Atenção e Hiperatividade versão para professores (ETDAH) (Scale for Attention Deficit Hyperactivity Disorder - teacher's version ). RESULTS: Data analysis indicated that the town under investigation does not offer any follow-up or support service specific for prematurity. The teaching methods in local early childhood education does not seem to be achieving desired levels because students from both groups had higher than expected difficulties in the handwriting tasks. The study also lends support to the relationship between preterm birth and unfavorable socioeconomic conditions. Regarding fine motor skills and handwriting, there was significant difference in some specific items of the tests, but not in the total scores, however the preterm group tended to present lower performance in handwriting, fine motor skills, global motor coordination and greater probability of signs of attention deficit and hyperactivity. Significant correlations were found between handwriting quality writing and the performance on some items of the motor tests. CONCLUSION: The results indicated that preterms are more likely to present motor and writing difficulties when compared to the full term peers, although with a larger sample the results might have reached statistical significance. Further studies should include larger and more homogeneous samples, with respect to gestational age and birth weight of the preterms.
Keywords: Terapia ocupacional; Prematuro; Escrita manual; Avaliação; Premature; Handwriting; Evaluation; Occupational therapy; CIENCIAS DA SAUDE::FISIOTERAPIA E TERAPIA OCUPACIONAL